Modifikasi Antena Vertical 2 Meter Band 2 X 5/8 Î› Pada Frekuensi 144-147 Mhz Dengan Menggunakan Sistem Sephasa. - Mahjud, Ichsan; Katu, Umar; Abidin, Zainal (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
All radios, both transmitting and receiving signals, need an antenna. So the role of the antenna is very important because the antenna can work as a transmitter or receiver, depending on the application of the antenna itself. For the transmitting antenna, it is hoped that it can cover a wide area, so that the receiver can access information in a wide area as well. With the addition of elements with antenna modifications, it will affect the radiance. In this study, the vertical 2 meter band 2 x 5/8 antenna using this phase system has many advantages such as a strong beam pattern in all directions, wide bandwidth and has a large gain and wider coverage area. Then the measurements and calculations of the antenna parameters that have been determined are carried out. From the data obtained at the time of measurement, it was found that the working frequency of the designed antenna was 145.9 MHz. it can be seen that the large amplification of the 2 meter band 2 x 5/8 vertical antenna against the standard 5/8 vertical antenna is 1 dB. The vertical 2 meter band 2 x 5/8 antenna has a bandwidth of 1.4 MHz and an omnidirectional radiation pattern, with a wider coverage area.